Adaptation and Validation of the School Climate and School Identification Measure-Student Scale (SCASIM-St) in a Sample of Chilean Adolescents - Gálvez-Nieto, José Luis; Vera-Bachmann, Daniela; Trizano-Hermosilla, Ítalo; Polanco-Levican, Karina; Briceño-Olivera, Claudio (Frontiers in Psychology, 2020)
The school climate construct has been linked to a series of positive outcomes in adolescence; however, the few validated instruments in Spanish have a fragile theoretical base. Consequently, the aim of this study was to adapt and validate the dual School Climate and School Identification Measure-Student (SCASIM-St) scale in a sample of Chilean adolescents. First, a linguistic adaptation of the instrument was completed, followed by a cross-sectional study; 1,456 students of both sexes participated in the study (41.1% boys and 58.9% girls), with an average age of 15.76 years (SD = 1.42), representing 17 secondary schools in Chile. Three confirmatory factor models were contrasted, the one with the best fit supported the originally proposed structure. The evidence of external criterion validity, confirmed through the Authoritative School Climate Survey (ASCS), showed a significant positive relationship between the two measures. This study verified the psychometric quality for the SCASIM-St scale, allowing for its use in the Chilean context. This instrument provides a measurement tool with a solid theoretical base that can be used in the Chilean context.